The resistivity image of the Upper Cretaceous Horné Belice Group: a case study from the Hranty section (Považský Inovec Mts., Western Carpathians) - PELECH, Ondrej; KUŠNIRÁK, David; BOŠANSKÝ, Marián; DOSTÁL, Ivan; PUTIŠKA, René; HÓK, Jozef (Contributions to Geophysics and Geodesy, 2017)
The Tatricum crystalline basement in the northern Považský Inovec Mts. contains several narrow tectonic slices with different rock composition. Some of them composed of the Upper Cretaceous mass flow deposits (the Horn´e Belice Group) are considered unique within the framework of the InternalWestern Carpathians and particularly within the Tatricum. Tectonic interpretation of their structural position is longer a matter of debate. Contrasting resistivity properties of the Hercynian mica schists and the Upper Cretaceous sandstones and shales were confirmed by the parametric geophysical measurements. The Hranty section, the structurally highest and most internal Upper Cretaceous tectonic slice was investigated by the electric resistivity tomography. Two longitudinal and two transverse resistivity profiles were measured and combined into a 3D image which suggests that the low resistivity Upper Cretaceous rocks form relatively shallow and flat lying structures folded and deformed between the crystalline basement slices.